The expert government of disaster in Africa: disaster science between states and international organisations - (:unkn) unknown (My University, 2013)
African dynamics in a multipolar World AEGIS-ECAS 2013, 5th European Conference on African Studies http://www.nomadit.co.uk/ecas/ecas2013/panels.php5?PanelID=2047
Keywords: African Research